Brainstem projections of neurons located in various subdivisions of the dorsolateral hypothalamic area—an anterograde tract-tracing study - Papp, Rege S.; Palkovits, Miklós (Frontiers in Neuroanatomy, 2014)
The projections from the dorsolateral hypothalamic area (DLH) to the lower brainstem have been investigated by using biotinylated dextran amine (BDA), an anterograde tracer in rats. The DLH can be divided into 3 areas (dorsomedial hypothalamus, perifornical area, lateral hypothalamic area), and further subdivided into 8 subdivisions. After unilateral stereotaxic injections of BDA into individual DLH subdivisions, the correct sites of injections were controlled histologically, and the distribution patterns of BDA-positive fibers were mapped on serial sections between the hypothalamus and spinal cord in 22 rats. BDA-labeled fibers were observable over 100 different brainstem areas, nuclei, or subdivisions. Injections into the 8 DLH subdivisions established distinct topographical patterns. In general, the density of labeled fibers was low in the lower brainstem. High density of fibers was seen only 4 of the 116 areas: in the lateral and ventrolateral parts of the periaqueductal gray, the Barrington's, and the pedunculopontine tegmental nuclei. All of the biogenic amine cell groups in the lower brainstem (9 noradrenaline, 3 adrenaline, and 9 serotonin cell groups) received labeled fibers, some of them from all, or at least 7 DLH subdivisions, mainly from perifornical and ventral lateral hypothalamic neurons. Some of the tegmental nuclei and nuclei of the reticular formation were widely innervated, although the density of the BDA-labeled fibers was generally low. No definitive descending BDA-positive pathway, but long-run solitaire BDA-labeled fibers were seen in the lower brainstem. These descending fibers joined some of the large tracts or fasciculi in the brainstem. The distribution pattern of BDA-positive fibers of DLH origin throughout the lower brainstem was comparable to patterns of previously published orexin- or melanin-concentrating hormone-immunoreactive fibers with somewhat differences.